2022
DOI: 10.1126/sciadv.abq2542
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the formation and transport of lunar impact glasses using the ages and chemical compositions of Chang’e-5 glass beads

Abstract: Impact glasses found in lunar soils provide a possible window into the impact history of the inner solar system. However, their use for precise reconstruction of this history is limited by an incomplete understanding of the physical mechanisms responsible for their origin and distribution and possible relationships to local and regional geology. Here, we report U-Pb isotopic dates and chemical compositions of impact glasses from the Chang’e-5 soil and quantitative models of impact melt formation and ejection t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 71 publications
3
9
0
2
Order By: Relevance
“…In the other scenario, the CE5 impact glasses could have lost most of the original water inventory of their precursors during their formation at high temperature, following which solar wind-derived water started diffusing inwards into these glass beads on the Moon's surface. This scenario is consistent with the notable lower abundances of volatile elements such as Na 2 O (most <0.05 wt%) and K 2 O (<0.06 wt%) in CE5 impact glasses compared with CE5 mare basalt fragments (Na 2 O ≈ 0.6 wt% and K 2 O ≈ 0.1-0.2 wt%, on average) 39 . This binary mixing model, between a water-poor but relatively high D/H endmember and a water-rich but extremely low D/H endmember, reproduces well the range of water abundances and δD values measured in CE5 impact glasses (Fig.…”
Section: Solar Wind Origin Of Watersupporting
confidence: 81%
See 3 more Smart Citations
“…In the other scenario, the CE5 impact glasses could have lost most of the original water inventory of their precursors during their formation at high temperature, following which solar wind-derived water started diffusing inwards into these glass beads on the Moon's surface. This scenario is consistent with the notable lower abundances of volatile elements such as Na 2 O (most <0.05 wt%) and K 2 O (<0.06 wt%) in CE5 impact glasses compared with CE5 mare basalt fragments (Na 2 O ≈ 0.6 wt% and K 2 O ≈ 0.1-0.2 wt%, on average) 39 . This binary mixing model, between a water-poor but relatively high D/H endmember and a water-rich but extremely low D/H endmember, reproduces well the range of water abundances and δD values measured in CE5 impact glasses (Fig.…”
Section: Solar Wind Origin Of Watersupporting
confidence: 81%
“…To investigate this possibility, we carried out a systematic characterization of the petrography, major element composition, Raman characteristics, water abundance and hydrogen isotope composition on the impact glass beads returned by the CE5 mission, aiming to identify and characterize the missing water reservoir on the Moon's surface. A recent geochronological study of CE5 impact glass beads has shown that they formed more or less continuously for the past 2 Gyr, with prominent peaks in formation ages at ~575 million years ago (Ma), 380 Ma, 68 Ma and 35 Ma, originating predominantly from a few 1-to 5-km-diameter impact craters in the Em4 (Eratosthenian-aged mare) basaltic unit where CE5 landed 39 . shadowed regions within Cabeus crater 11 .…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Lunar glasses, which are a common component in lunar regolith, originate mainly from meteorite impacts ( 13 ). They have experienced extremely long time scale’s weathering and aging (about millions to billions of years) but maintained the glassy nature ( 14 , 15 ). As weathering mainly affects the surface region (~100 to 200 nm) of lunar glasses ( 16 ), the inner part of lunar glasses could be the ideal model to evaluate the long-term aging effects of glasses.…”
Section: Introductionmentioning
confidence: 99%